Recurrent Vaginal Prolapse in a Crossbred Cow Due to Cystic Gartner’s Ducts - GHUMAN, S P S; NANDA, A S; PRABHAKAR, S; GANDOTRA, V K; HONPARKHE, M (The Indian Journal of Animal Reproduction, 2023)
A rare case of cystic Gartner’s duct associated with recurrent vagina] prolapse and its management is reported.